Predictors of choice of abortion method among women attending abortion clinic in a government hospital in Nepal - Basnet, Bidhya; Adhikari, Sunaina; Kumari Mandal, Punam; Thapa, Sheela; Kumari Acharya, Devaka (Journal of Kathmandu Medical College, 2023)
Background: Abortion has long been a method of terminating an unintended pregnancy globally and can be provided through either medical or surgical ways. Factors affecting the choice of abortion method appear to be numerous and complex. Objectives: This study aimed to identify the predictors of choice of abortion methods among women attending abortion clinic. Methods: A cross sectional analytical study conducted in Paropakar Maternity and Women’s Hospital, Thapathali among 132 clients, at nine weeks of gestation.Samples were selected using consecutive sampling technique. Data were collected for the period of one month (2016 February 27 to March 27) using a semi-structured questionnaire. Descriptive and Inferential statistics (bivariate analysis, multivariate analysis) were used to find the predictors of choice of methods of abortion and final model was selected. Results: Among the women attending for abortion 68 (51.5%) had chosen surgical over medical method of abortion. Eight to nine weeks of gestation (OR: 6.043, 95% CI: 1.636-22.316), predetermined choice on surgical method of abortion (OR: 13.871, 95% CI: 2.419-79.528) and inconvenient to revisit the clinic (OR: 4.299, 95% CI: 1.127-16.397) were found to be the predictors of choice of abortion methods. Conclusion: Predetermined choice of particular method, period of gestation and revisit to the clinic are the major predictors of choice of surgical over medical method of abortion. The choice of abortion methods is influenced by various factors so offering the choice will help in developing the women centered abortion care.